Comparative Study of Harris and Active Contour using Viola-Jones Algorithm for Facial Landmarks Detection - El Rhazi, Manal; Zarghili, Arsalane; Majda, Aicha (Transactions on Engineering and Computing Sciences, 2017)
In this paper, we present a comparative study of two methods: Harris corners detector (H) and Active Contour detector (A.C) using Viola-Jones algorithm (V.J) for facial landmarks (eyes, nose, mouth) corners detection. These methods were implemented on two face databases; ECVP and FEI databases with combination of two methods (V.J + H) and (V.J + A.C). Experimental results showed that (V.J +A.C) gives a higher rate of detection than (V.J + H) method.